Differences in COVID-19 testing and adverse outcomes by race, ethnicity, sex, and health system setting in a large diverse US cohort. - Celeena Jefferson; Eric Watson; Julia M Certa; Kirsha S Gordon; Lesley S Park; Gypsyamber D'Souza; Lorie Benning; Alison G Abraham; Deana Agil; Sonia Napravnik; Michael J Silverberg; Wendy A Leyden; et al. (PLoS ONE, 2022)
Background Racial/ethnic disparities during the first six months of the COVID-19 pandemic led to differences in COVID-19 testing and adverse outcomes. We examine differences in testing and adverse outcomes by race/ethnicity and sex across a geographically diverse and system-based COVID-19 cohort collaboration. Methods Observational study among adults (≥18 years) within six US cohorts from March 1, 2020 to August 31, 2020 using data from electronic health record and patient reporting. Race/ethnicity and sex as risk factors were primary exposures, with health system type (integrated health system, academic health system, or interval cohort) as secondary. Proportions measured SARS-CoV-2 testing and positivity; attributed hospitalization and death related to COVID-19. Relative risk ratios (RR) with 95% confidence intervals quantified associations between exposures and main outcomes. Results 5,958,908 patients were included. Hispanic patients had the highest proportions of SARS-CoV-2 testing (16%) and positivity (18%), while Asian/Pacific Islander patients had the lowest portions tested (11%) and White patients had the lowest positivity rates (5%). Men had a lower likelihood of testing (RR = 0.90 [0.89-0.90]) and a higher positivity risk (RR = 1.16 [1.14-1.18]) compared to women. Black patients were more likely to have COVID-19-related hospitalizations (RR = 1.36 [1.28-1.44]) and death (RR = 1.17 [1.03-1.32]) compared with White patients. Men were more likely to be hospitalized (RR = 1.30 [1.16-1.22]) or die (RR = 1.70 [1.53-1.89]) compared to women. These racial/ethnic and sex differences were reflected in both health system types. Conclusions This study supports evidence of disparities by race/ethnicity and sex during the COVID-19 pandemic that persisted even in healthcare settings with reduced barriers to accessing care. Further research is needed to understand and prevent the drivers that resulted in higher burdens of morbidity among certain Black patients and men.